Epistemic Games of Moderate Physics-Capable Students in Completing Electrical Circuit Problems - M. Dewi Manikta Puspitasari; Anita Sari Wardani; Lilia Sinta Wahyuniar (Universitas Lambung Mangkurat, 2020)
The students need a learning strategy that is compatible to develop electrical circuit problems completion. Additionally, problem-solving strategy (epistemic game) will develop a learning process that can stimulate the completion of physics. This case encourages the researcher to determine the epistemic game of moderate physics-capable students in solving electrical circuit problems. Moreover, it is qualitative research, and the participant of the research is the students who learn the electrical circuit. Moderate physics-capable students (4 moderately capable students out of 13 students) based on their physics understanding test results. Test and interview were used by the researcher to collect data. The test consists of a physics understanding test and an electrical circuit test. The physics understanding test is used to determine the level of students’ physics understanding, while the electrical circuit test is used to determine students’ epistemic games to solve the problems. The research finding showed the epistemic game of moderate physics-capable students was obtained from the analysis result of the electrical circuit test and interview. The analysis result of the first test, the second test, the third test, and the seventh test showed that the game used to solve problems was transliteration to mathematics. Meanwhile, the students used mapping mathematics to meaning and transliteration to mathematics to solve the problems in the fourth test. The analysis result of the fifth test and the eight test showed that the students used mapping mathematics to meaning to solve the problems. Furthermore, the sixth test was completed by mapping meaning to mathematics.